2022
DOI: 10.1021/acs.organomet.2c00171
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 Reduction Using an Iron–Bipyridyl Complex Supported by Two Phosphines for Improving Catalyst Durability

Abstract: We herein report that an iron (Fe) complex bearing a tetradentate PNNP ligand catalyzes photochemical carbon dioxide (CO2) reduction to produce mainly carbon monoxide (CO) together with formic acid (HCO2H) combined with a photosensitizer. The structurally bulky phosphine moieties stabilized the catalyst and improved its durability over a few days (∼72 h) to give the turnover number (TON) of 397. Operando subnanosecond laser-induced transient absorption measurements allowed us to observe the direct electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…OPC 3 , which was critical to solving this issue, has an ESOP of −2.1 V vs SCE, which is higher than that of fac -[Ir­(ppy) 3 ] ( E * ox = −1.7 V vs SCE). In contrast, the excited-state lifetime of 3 was <3 ns, which was much shorter than that of fac -[Ir­(ppy) 3 ] (τ = 1.3–1.9 μs). Since it is important to determine whether the ESOP or excited-state lifetime is more essential to organic reactions, Hawker and Alaniz et al compared 3 and fac -[Ir­(ppy) 3 ] and demonstrated that 3 is more effective in the hydrodehalogenation of aryl iodides and bromides.…”
Section: Recent Development Of Phenothiazine Dihydrophenazine and Phe...mentioning
confidence: 79%
See 3 more Smart Citations
“…OPC 3 , which was critical to solving this issue, has an ESOP of −2.1 V vs SCE, which is higher than that of fac -[Ir­(ppy) 3 ] ( E * ox = −1.7 V vs SCE). In contrast, the excited-state lifetime of 3 was <3 ns, which was much shorter than that of fac -[Ir­(ppy) 3 ] (τ = 1.3–1.9 μs). Since it is important to determine whether the ESOP or excited-state lifetime is more essential to organic reactions, Hawker and Alaniz et al compared 3 and fac -[Ir­(ppy) 3 ] and demonstrated that 3 is more effective in the hydrodehalogenation of aryl iodides and bromides.…”
Section: Recent Development Of Phenothiazine Dihydrophenazine and Phe...mentioning
confidence: 79%
“…68−70 Complexes of earth-abundant Fe(II) were also used as effective CO 2 reduction sites, which were difficult to be realized without photosensitization using fac-[Ir(ppy) 3 ]. 71 Our impression is that the replacement of PMPCs including fac-[Ir(ppy) 3 ] with OPCs would satisfy both the requirements in which the usage of ubiquitous/common elements and the development of sufficiently strong reducing agents should be more significantly vitalized. Moreover, while the photocatalytic transformation of "inorganic" CO 2 has reached a rather advanced stage, 72−77 various longstanding challenges remain in the conversion of highly oxidized/oxygenated "organic" compounds, which are highly abundant in renewable biomass feedstocks, 78−81 into more reduced forms for use as energy-rich platform chemicals using photoexcited electrons with high reducing ability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these homogeneous photochemical CO 2 reduction systems generally focus on CO formation, whereas the selective production of HCO 2 H, a widely used energy-enriched compound in both laboratory and industry, is rarely reported. [35][36][37][38][39][40] A major challenge for the CO 2 reduction to generate HCO 2 H results from its disfavored thermodynamics compared to the production of CO since the redox potential for CO 2 /CO (−0.53 V in water, pH = 7) is less negative than that of CO 2 /HCO 2 H (−0.61 V in water, pH = 7). 41,42 Plus, the undesired hydrogen evolution reaction (H + / H 2 , with a redox potential of −0.41 V in water, pH = 7) seems unavoidable during the CO 2 reduction in aqueous medium, as it is thermodynamically more favorable than CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%